The Scope of Contemporary Islamic Legal Thought: A Methodological Analysis and a Comparative Study of Indonesia and Malaysia - Mursyida, Aisyah Nurhalisha; Syarifuddin, Syarifuddin; Murtadho, Ali (Universitas Islam Negeri Sumatera Utara, 2026)
This article examines the scope of contemporary Islamic legal thought and its methodological approaches through a comparative study of Indonesia and Malaysia. Using qualitative library research with a normative-comparative approach, this study analyzes academic literature, fatwas, and legal regulations related to Islamic law in both countries. The findings show that although both countries employ maqāṣid al-syarī‘ah as a methodological framework, they differ in orientation. Indonesia tends to adopt a more plural and academic approach by incorporating hermeneutical and socio-historical perspectives, while Malaysia emphasizes a legal-formal approach through state institutions and Syariah courts. These differences indicate that contemporary Islamic legal thought is contextual and shaped by socio-political structures and legal systems.